Предмет: Математика,
автор: eozin
Найти cos^6x-sin^6x, если cos2x=0,4
Ответы
Автор ответа:
0
Решение:
cos^6x-sin^6x=(cos^2x)^3-(sin^2x)^3=
= ((1+cos(2x))/2)^3-((1-cos(2x))/2)^3=
= ((1+0,4)/2) ^3-((1-0,4)/2)^3=
=(0,7)^3-(0,3)^3=
=0,343-0,027=0,316.
Ответ: 0,316.
cos^6x-sin^6x=(cos^2x)^3-(sin^2x)^3=
= ((1+cos(2x))/2)^3-((1-cos(2x))/2)^3=
= ((1+0,4)/2) ^3-((1-0,4)/2)^3=
=(0,7)^3-(0,3)^3=
=0,343-0,027=0,316.
Ответ: 0,316.
Автор ответа:
0
Спасибо!
Похожие вопросы
Предмет: Русский язык,
автор: inkarniyaz08
Предмет: Геометрия,
автор: eva4541
Предмет: Окружающий мир,
автор: gleb93788
Предмет: Математика,
автор: rafaellka2
Предмет: Литература,
автор: Виктория2241